(untitled) (Fiep Bulletin - online, 2012)
The present article approaches the debate concerning the influence exercised by the media in the construction of the individuals’ of the society sociocultural identities, mainly in children and adolescents, founding starting from the athletes’ illustration, models of behavior, that get to constitute social representations, per times called to you factor political - economical, that you/they cart in the breaking of the sociocultural identities because of the transmit of the sport of high level as valve of escape of the socioeconomic problems that they affect most of the population. The intended objective is to demonstrate the importance of that debate in the current society, mainly in the Physical education tends in view the appeal of the media every time larger around the consolidation of the area through the income sport. For that, the basic bibliographical research was used, starting from consultations of extracted texts of the internet, as goods, newspapers and magazines, discussion in classroom, added the teacher’s of the discipline Sociological Foundations orientation in the Physical education.